Tears of pearl - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2010)
Honeymooning in late-nineteenth-century Turkey, British diplomats Lady Emily and Colin Hargreaves investigate the murder of a harem girl who is identified as the kidnapped daughter of an embassy worker.